Multibeam Antennas Based on 3-D Discrete Lenses With Magnified Field-of-View - Lisa Berretti; Renaud Loison; Esteban Menargues; Lucas Polo-Lopez; Giovanni Toso; Maria Garcia-Vigueras (IEEE Open Journal of Antennas and Propagation)
A new type of beamforming network (BFN) based on three-dimensional (3D) discrete lenses is introduced and numerically analyzed in this paper as an antenna system capable of generating multiple beams within a large Field-of-View (FoV). To enhance scanning capabilities, these lenses have their back part and associated feed array magnified relative to the front part. It is also shown that the radiating elements constituting the front part of the lens, due to the shape of their element factor, tend to limit the pointing direction of the overall antenna pattern, but their influence decreases as the lens dimension. Accordingly, a large front array is chosen to scan wide angles and mitigate this limitation. For the preliminary dimensioning and design of the entire BFN, a Geometrical Optics (GO) technique is employed. Subsequently, a rigorous methodology exploiting boundary conditions in the planes of symmetry is implemented to simulate the full-wave behavior of the front array of the lens, which is challenging due to limited computational resources for large arrays. This methodology, which also exploits the even/odd concept, is validated using a small array as a test case. By employing both the GO technique and rigorous full-wave analysis, it is numerically verified that this type of lens system can produce beams pointing up to 70° from the boresight direction while maintaining good levels of cross-polar discrimination in all azimuthal planes. Additionally, numerical evidence shows that these magnified lenses can increase their FoV compared to lenses with equal back and front sizes, reaching approximately 50° of scanning. The multibeam features of this lens are also numerically validated.